Nanosized‐Layered LiVO2 Prepared from Peroxo‐Polyvanadic Acid and Its Electrochemical Properties. Issue 11 (4th October 2014) - Tsuyumoto, Isao; Nakakura, Yuya; Yamaki, Satoru; Bosacka, M.
<x xml:space="preserve">Abstract</x> Nanosized‐layered rock‐salt LiVO2 was prepared by a new method from peroxo‐polyvanadic acid. The X‐ray diffraction pattern was well fitted with the space group R−3m in the Rietveld analysis and the crystallite size was estimated at 47 nm. The electrochemical properties as cathode materials for lithium ion batteries were investigated. The specific capacity of LiVO2 was greatly improved to 149 mAh/g under the current density of 149 mA/g, in comparison with that of the conventional LiVO2 below 50 mAh/g prepared by the solid‐state reactions.